Enhancing Students’ Oral Communication By Using Communicative Language Teaching (CLT) - Ahmad Wael; Dian Saputra; Eka Setyawati (Qalam : Jurnal Ilmu Kependidikan, 2019)
This article aims at providing students’ oral communication in speaking class. There were two specific purposes to gain the data namely to find out the effects of Communicative Language Teaching (CLT) in teaching oral communication especially in speaking ability and to disclose the responses of students in the learning process by using Communicative Language Teaching (CLT). In order to obtain the comprehensive data, the writers used performance test and questionnaire with 32 respondents on speaking class. This research was applied in quantitative method. The writers used the design of interact group comparison. The result showed that there was a significant effect on the use of CLT approach. It was proven that t observation was bigger than   t table; t observation was 2.98 while t table was 2.021 (2.98> 2.021). Most of the students  agreed if CLT was applied in teaching-learning activites, especially in speaking class because it could help them in improving their ability in oral communication. The results of their opinion towards the application of CLT were expressed by chosing option 4 (agree) and 5 (strongly agree) in every indicator. For indicator 1 and 10, students tent to choose option 5 (strongly agree) with the percentage of 56.3 and the mean of 2.8. In indicator 2 and 4, the students tent to choose option 5 with the percentage of 59.4 and the mean of 3.0. In indicator 3 and 7, the students tent to choose option 4 (agree) with the percentage of 62.5, and mean score of 2.5. For indicator 5 and 6, the students chose option 5 with the percentage of 50.0 and mean score of 2.5. For indicator 8 and 9, most of the students tent to choose option 5 (strongly agree). The percentage and mean score were different. In indicator 8, the percentage was 56.3 with the mean score of 2.3 whereas in indicator 9, the percentage was 68.8 which the mean score of 2.8 more of the respondents were strongly agree with the application of CLT approach in speaking class. It made the students interestend in following  speaking class and the students have confidence to speak with other friend or lecturer inside or outside the classroom.